2011
DOI: 10.1007/s10452-011-9365-9
|View full text |Cite
|
Sign up to set email alerts
|

Temporal stability of marine phytoplankton in a subtropical coastal environment

Abstract: We investigated the temporal stability of phytoplankton at a subtropical coastal site for 9 months by conducting chlorophyll and flow cytometric measurements at relatively high frequency (roughly at 2-5 day interval). Phytoplankton cells were grouped based on their sizes obtained from flow cytometric signals. We also conducted dilution experiments to estimate the growth and grazing mortality rates of different phytoplankton groups to assess whether the temporal stability of phytoplankton abundances was related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…3B ). Diatoms and Cyanophyceae have requirements for warm temperature, high nutrient levels, and a certain level of salinity 41 42 43 . Indeed, a recent study showed that the contribution of diatoms to water column productivity in oceans is positively correlated with sea surface temperature 42 .…”
Section: Resultsmentioning
confidence: 99%
“…3B ). Diatoms and Cyanophyceae have requirements for warm temperature, high nutrient levels, and a certain level of salinity 41 42 43 . Indeed, a recent study showed that the contribution of diatoms to water column productivity in oceans is positively correlated with sea surface temperature 42 .…”
Section: Resultsmentioning
confidence: 99%
“…are thought to be fast-growing r-strategists that respond quickly to nutrient pulses 32 . In contrast, slow-growing eukaryotic algae (including Isochrysis ) can be regarded as K-strategists that respond less quickly to environmental disturbances, but are superior competitors under low nutrient conditions 32 . Likewise, these two plankton groups generally have different temperature response patterns.…”
Section: Discussionmentioning
confidence: 99%
“…While contribution of other unmeasured factors, such as the depth of nutricline, in our study cannot be ruled out ( 10 ), another important reason could be that most diatom species are r strategists, with high growth rate at a favorable environment. Rapid nutrient uptake by these dominant diatom species would weaken the correlation between nutrient concentrations and community structures ( 5 , 60 ), which is different from K strategists (e.g., haptophytes), which have low growth rates, and r strategists ( Synechococcus ), which mainly rely on physical factors ( 30 , 61 ). Therefore, direct estimation of environmental selection pressure using in situ environmental factors potentially leads to an underestimation with large proportion of unexplained variations, especially for r strategists relying on nutrients or other easily depleted factors ( 11 , 53 , 62 ).…”
Section: Discussionmentioning
confidence: 99%